تأثير الخطاب السياسي للسلطان قابوس في بناء محتوى البرامج الاقتصادية في التلفزيون العماني - Amal Mohamed Said Alnoofli (Universiti Sains Islam Malaysia, 2024)
This study aims to analyse the impact of the political discourse of Sultan Qaboos between the years of 2008 and 2015 in building the content of economic programs on Omani Television, and the study intend to scrutinize the most important economic theses. In order to classify the paths of arguments involved in the discourse, in addition to exploring the indication frames, moreover analysis content of the “ Economic Vision” program and classification of the issues that have been raised , to observe how the political discourse push the program to adopt Specific economic issues. The study based on descriptive studies, which tends to implement the content analysis, relied on two types of analysis. The first analysis of the political discourse, the second program content analysis, and using of a series of research tools represents by the forms of discourse analysis and content analysis to collect the necessary data. The study based on a planned sample of 13 discourses to Sultan Qaboos from years of 2008 to 2015 and 33 episodes of the program “ Economic Vision “. The study reached a series of results, the most important: the issues of the political discourse of Sultan Qaboos reflected on the program content by 23.5% , while the issues that filled the Sultan Qaboos discourses were at the center of economic growth and strategy. And the results of the study point to that 61.8% of the contents of the program do not match to the contents of the discourse while 11.8% discussed part of the issues of discourse.